Gestión de la imagen corporativa de Transcomerinter a partir del atributo seguridad en la operación de transporte de carga terrestre - Pinargote Santos, Arely Tatiana (2018)
The present title work has been developed with the aim of managing the image corporate of Transcomerinter from the security attribute, through the implementation of strategic communication and in this way ensure the loyalty of its current and future customers. Transcomerinter is a land transport company with more than 20 years in the Ecuadorian market and successful business carried out with important multinationals inside and outside the country, for this reason, an investigation was carried out in which the categories of image, identity and reputation. Through the structured interview it was allowed to know in their different audiences the perception that the company has regarding the activities carried out and to discover which strategies are the pertinent ones to improve the flaws evidenced with the tool used. The objectives and methodology implemented have been supported by a review of the literature of authors based on corporate communication research aimed at guiding the tools, strategies and actions to be implemented through the best channels. Taking into account the data obtained, the document concludes with a communicational proposal in which objectives, publics, strategies, actions have been developed, with the final goal of this title work to guide Transcomerinter to manage its image in accordance with the proposals established by authors, who guide on the proper use of media and communication tools.